Bioeconomy: Fermented Waste Management and Pectinases Purification from Thermomyceslanuginosus - Makky, Essam A.; M. M., Yusoff (Faculty Mechanical Engineering, UMP, 2014)
Sugar-cane bagasse (SCB) is used for pectinases production from Thermomyceslanuginosus at 55°C under solid-state fermentation (SSF).The study aims to purify total PNL and PL enzymes produced from SCB as the sole carbon source at 55°C using microbial fermentation technology, and to evaluate the fermented bagasse residuals as fertilizer for the purpose of combatting soil desertification and then detect the amino acids content. The total PNL and PL enzymes were purified and showed two identical peaks, each representing one enzyme. Biotechnological applications of fermented bagasse obtained at 55°C,used as biofertilizer at different concentrations, were cultivated with Zea mays for 30 days to indicate the growth on sandy soil, and induced plant growth which gives an indication of applying the present biofertilizer in reclaimed sandy soils. Only 13 amino acids were detected and were obviously glycine/histidine-containing enzymes. It is apparent that the fermented bagasse successfully improved the sandy soil as biofertilizer and total PNL and PL enzymes were accurately purified at thermophilic conditions under SSF.